Phase II trial of biweekly cetuximab and irinotecan as third‐line therapy for pretreated KRAS exon 2 wild‐type colorectal cancer. Issue 8 (13th July 2018) - Osumi, Hiroki; Shinozaki, Eiji; Mashima, Tetsuo; Wakatsuki, Takeru; Suenaga, Mitsukuni; Ichimura, Takashi; Ogura, Mariko; Ota, Yumiko; Nakayama, Izuma; Takahari, Daisuke; Chin, Keisho; Miki, Yoshio; et al.
Abstract : Efficacy and safety of biweekly cetuximab plus irinotecan were evaluated to provide guidance for its use in Japan as third‐line treatment for pretreated metastatic colorectal cancer (mCRC) patients harboring wild‐type KRAS exon 2. Objective response rate (ORR) was used as primary endpoint based on an expected proportion of 0.23 with confidence width of 0.298 (95% CI, 0.105‐0.403), which showed 35 to be the minimal participant number. Forty patients, refractory to first‐ and second‐line chemotherapy containing irinotecan, oxaliplatin, and fluoropyrimidine, were enrolled. ORR and disease control rate were 25.0% (95% CI: 11.5‐38.4) and 72.5% (95% CI: 56.8‐86.4), respectively. Median progression‐free survival (PFS), overall survival (OS), and number of courses were 5.70 months (95% CI: 2.7‐7.9), 15.1 months (95% CI: 11.8‐19.0), and 10.5 (range: 3.0‐31.0), respectively. Grade 3 adverse events were skin toxicity (12.5%), diarrhea (10.0%), neutropenia (5.0%), febrile neutropenia (5.0%), nausea (5.0%), anorexia (5.0%), and fatigue (2.5%). C max mean was 723.2 μg/mL after first dose. High area under the curve (AUC)last variance was associated with t1/2 range of 131.2‐1209.6 hours (median, 174.4 hours). Early tumor shrinkage (ETS) and median depth of response were 25.0% and 13.0%, respectively. Mutation frequencies in KRAS exon 3 or 4, NRAS, BRAF, and PIK3CA were 5.5%, 2.7%, 8.3%, and 5.5%, respectively. Multivariate Cox regression analysis assessed whether any gene mutations and ETS are predictors for PFS, and whether performance status, synchronous metastasis, and ETS are predictors for OS. Importantly, the data provide guidance for a biweekly cetuximab plus irinotecan regimen in mCRC patients. Abstract : Efficacy and safety of biweekly cetuximab plus irinotecan treatment were similar in patients from Japan and in a western population.